Value relevance and changes in accounting standards: A review of the IFRS adoption literature - Japhet Imhanzenobe (Cogent Business & Management, 2022)
Share prices reflect available financial information about those firms and a substantial amount of these information come from financial statement figures. The informativeness of the reported earnings and book values in financial statements depend on accounting standards that govern their preparation, thus accounting standards could influence the informativeness of financial statement figures as well as the degree to which investors consider these figures in making investment decision. This relevance of accounting figures to investors is referred to in existing literature as value relevance. This study investigated the relationship between value relevance and the adoption of International Financial Reporting Standards (IFRS). Most pioneer studies on value relevance and changes in accounting standards discovered a decline in the value relevance of financial statements in the US while most of the reviewed studies that address IFRS specifically discovered an increase in value relevance in the respective markets after adoption of IFRS. A few studies also reported a lack in improvement of value relevance following IFRS adoption but attributed the results to anomalies like government interference, mock compliance, improper enforcement, firm-specific differences and business changes that are outside the scope of financial reporting. The study recommended the adoption of IFRS standards as a possible factor that can improve value relevance.
Keywords: 650; accounting standards; adaptive market hypothesis; IFRS adoption; transparency; Value relevance